Sharia Capital Market as A Driver of Economic Growth After The Covid-19 Pandemic Crisis in Indonesia - Iman Maulana, Nurul; Haryadi, Rofiq Noorman; Supriatal, Supriatal (International Journal of Sharia Business Management, 2025)
The COVID-19 pandemic has severely impacted Indonesia’s economy, triggering contractions in key sectors and posing challenges to recovery efforts. Amidst this crisis, the Sharia capital market has emerged as a promising driver for sustainable economic growth, grounded in Islamic principles that prohibit riba (interest), gharar (uncertainty), and maysir (gambling). This study explores the strategic role of the Sharia capital market in supporting Indonesia's post-pandemic economic recovery. Using a qualitative approach through literature review, the research analyzes the contribution of Sharia-compliant financial instruments—such as sukuk, Sharia stocks, and investment funds—in revitalizing Sharia-oriented sectors including halal industry, renewable energy, Islamic finance, and MSMEs. The study identifies factors influencing investor participation, highlights existing challenges such as limited public literacy and policy support, and offers strategic recommendations for policymakers to enhance the market’s effectiveness. The findings underscore that the Sharia capital market not only offers ethical and inclusive financial solutions but also supports long-term national development goals through equitable and resilient economic systems.